Analisis Jumlah Puskesmas dan Persebaran Tenaga Kesehatan di Kabupaten Kendal Menggunakan Pendekatan Sistem Informasi Geografis - Muhammad Mukti Rimawan (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study aims to visualize the number of puskesmas and distribution of health workers in Kendal Regency from 2020 to 2022 using a Geographic Information System (GIS) based website approach. The research method used is collection of spatial and non-spatial data which are then processed using GIS software. Spatial data refers to data that refers to the Earth’s conditions, such as coordinate points. Meanwhile, non-spatial data in GIS is data that is not related to geography, usually in tabular form. The result of this study are expected to assist in the development and equal distribution of health facilities.